The Effect of Tax Audit and Tax Collection on Increasing Corporate Taxpayer Compliance at KPP Pratama Pasar Rebo, East Jakarta - richardo, Richardo Abessy Gultom; Elly Rasyid; L.Toruan, Rutman (Universitas Kristen Indonesia, 2024)
This study discusses the effects of tax audits and tax collections on increasing corporated tax payer compliances at KPP Pratama Pasar Rebo East Jakarta (2017-2020), which aim to test and analyze effects of tax audits and tax collection on increasing corporated tax payer compliances. This research method uses descriptive statistical methods. These studies were test use data analyst method including descriptive analyst test, classic assumptions test, hypothesis testing, multipled linear regression analyst and coefficients of determination testing. The result of these studies shows that significances of effects of tax audits on increasing corporate tax payer compliance at KPP Pratama Pasar Rebo, East Jakarta (2017-2020) was 0.018 <0.05 and t (count) value was 2.515 > t (table) 1.706 so that it could be This means that tax audits have a positive effect on corporate tax payer compliances. Furthermore, the effect of tax collection on corporate tax payer compliance is 0.000 <0.05 and t (count) values is 11.988 > t (table) 1.706, in other words that taxes collection has a positive effect on corporate tax payer compliances. Likewise, it is known that taxes audit and tax collections is 0.000 <0.05 and F value (count) 81.506 > F value (table) 3.354 so it can be concluded that taxes audit and tax collections have a simultaneous effect on increasing corporate tax payer compliances. Keywords: Tax Auditor, Tax Collection, Corporate Tax payer Compliances